2017
DOI: 10.1177/0194599817721454
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of Tympanostomy Tubes in the Boston Metropolitan Area: Are the AAO‐HNSF Guidelines Being Met?

Abstract: Introduction Otitis media (OM) is the most common reason children receive general anesthesia, with bilateral tympanostomy tube (TT) insertion the second most common surgery in children. Prior research suggests overuse of TT. As part of a project designed to improve appropriateness of OM referrals, we evaluated appropriateness of TT insertion in a patient cohort. Methods Patients younger than 9 years with initial otolaryngology (ORL) visits in academic and private office settings for OM from January 1, 2012, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…3 Subsequent research showed excellent adherence by clinicians to guideline recommendations for tube insertion and for watchful waiting to reduce unnecessary surgery. 4-6 These recommendations have been adopted, in part, by other countries publishing guidelines on OME that secondarily discuss tympanostomy tubes. 7-11 As such, the AAO-HNSF guideline remains the only publication explicitly focused on tympanostomy tube indications and managing children who receive tubes.…”
Section: Update Rationale and Scopementioning
confidence: 99%
See 2 more Smart Citations
“…3 Subsequent research showed excellent adherence by clinicians to guideline recommendations for tube insertion and for watchful waiting to reduce unnecessary surgery. 4-6 These recommendations have been adopted, in part, by other countries publishing guidelines on OME that secondarily discuss tympanostomy tubes. 7-11 As such, the AAO-HNSF guideline remains the only publication explicitly focused on tympanostomy tube indications and managing children who receive tubes.…”
Section: Update Rationale and Scopementioning
confidence: 99%
“…1 An update was necessitated by an .5-year lapse and by subsequent original research and systematic reviews that might modify existing recommendations or support new ones. Changes in content and methodology from the prior guideline include the following: New evidence from 6 CPGs, 18 systematic reviews, and 27 randomized controlled trials (RCTs) Emphasis on patient education and shared decision making with new tables of counseling opportunities and frequently asked questions Expanded key action statement (KAS) profiles to explicitly state quality improvement opportunities and implementation considerations New flowchart to clarify decision making and show the relationships among KAS recommendations A new strong recommendation that the surgeon or designee should examine the ears of a child within 3 months after tympanostomy tube insertion to assess outcomes and should educate families regarding the 1 SUNY Downstate Health Sciences University, Brooklyn, New York, USA; 2 School of Medicine, Johns Hopkins University, Baltimore, Maryland, USA; 3 Virginia Mason Medical Center, Seattle, Washington, USA; 4 Cleveland Clinic Foundation, Cleveland, Ohio, USA; 5 University of Mississippi Medical Center, Jackson, Mississippi, USA; 6 Baylor College of Medicine-Texas Children's Hospital, Houston, Texas, USA; 7 Pomona Pediatrics, Boston Children's Health Physicians, Pomona, New York, USA; 8 New York Medical College, Valhalla, New York, USA; 9 Cincinnati Children's Hospital Medical Center, Cincinnati, Ohio, USA; need for routine, periodic follow-up to examine the ears until the tubes extrude A new option for the clinician to perform adenoidectomy as an adjunct to tympanostomy tube insertion for children with symptoms directly related to the adenoid (adenoid infection or nasal obstruction) or in children aged 4 years or older to reduce future incidence of recurrent otitis media or the need for repeat tube insertion A new recommendation against placing long-term tubes as initial surgery for children who meet criteria for tube insertion unless there is an anticipated need for prolonged middle ear ventilation beyond that of a short-term tube A new recommendation against routinely prescribing prophylactic antibiotic ear drops after tympanostomy tube surgery to prevent or reduce otorrhea Addition of intellectual disability, learning disorder, or attention-deficit/hyperactivity disorder to the list of risk factors that place children who have otitis media with effusion (OME) at increased risk for developmental difficulties (at-risk child) Updated categories of normal to mild hearing loss in children, with normal hearing as 0 to 15 decibels (dB), slight hearing loss as 16 to 25 dB, and mild hearing loss as 26 to 40 dB…”
Section: Update Rationale and Scopementioning
confidence: 99%
See 1 more Smart Citation
“…5 Subsequent research showed excellent adherence by clinicians to guideline recommendations for tube insertion and for watchful waiting to reduce unnecessary surgery. 6-8 These recommendations have been adopted, in part, by other countries publishing guidelines on OME that secondarily discuss tympanostomy tubes. 9-13 As such, the AAO-HNSF guideline remains the only publication explicitly focused on tympanostomy tube indications and managing children who receive tubes.…”
Section: Update Rationale and Scopementioning
confidence: 99%
“…3 In 2013, the first, national guidelines on tympanostomy tube indications were published, 4 with subsequent rates of adherence by clinicians estimate at 95%. 5 The current guidelines, however, are limited in scope and deal primarily with indications and global management issues, remaining silent, in many cases, on the pragmatic challenges and controversies encountered by clinicians. Moreover, attitudes toward tubes remain fluid and continue to evolve, leading to a recent position statement on tube insertion in office settings without general anesthesia.…”
Section: Introductionmentioning
confidence: 99%